Threats to Decolonial Immanent Ethics - Maistry, Suriamurthee Moonsamy (African Journal of Inter/Multidisciplinary Studies, 2021)
The last three decades have witnessed a distinct shift in the identity and purpose of higher education across the world. From being a site for predominantly public institutions offering a Humboltian social good, higher education has morphed towards narrowly responding to powerful national economic growth imperatives. Both public and private institutions now compete aggressively along neoliberal market principles to provide an economic good. African higher education is not immune to such persuasions. There is now aggressive competition for students, personnel, and physical and economic resources. An insidious performativity discourse has become normalised, emphasising outcomes, throughputs, and performance measurements. This culture is likely to impact the work of the academe, especially as it relates to research and scholarship, is without question. There is little contention that the understanding and application of fundamental ethical principles in the conduct of research is likely to be threatened. Contemplating (South) African research ethics in institutions whose governance is inspired by the traditional colonial (Anglo) model that pledges allegiance to a heterosexual white male value system, which requires a critical deconstruction in the face of transformation and social cohesion discourses that urge the rejection of race and race markers and a discounting of identity politics. This conceptual article considers how we might mitigate the deleterious effects of a neoliberal higher education milieu and the marginalising of (Black) race as a compelling socio-cultural resource. This paper argues for a transition from a narrow, technical, ethical compliance towards understanding and applying Deleuzian immanent ethics.